Erroneous values for the total white cell count and ESR in patients with cryoglobulinaemia. Issue 10 (October 1976) - Haeney, M R
Abstract : Temperature dependent fluctuations in the erythrocyte sedimentation rate were noted during the assessment of one patient with symptomatic cryoglobulinaemia. Two patients with this condition were found to have erroneously high leucocyte counts when estimated by the Model S Coulter Counter. The artefact was directly related to the degree of exposure to cold before the estimation was performed and appeared to be due to the formation of microaggregates of cryoglobulin and fibrinogen.